POTENSI Azotobacter sp. ST.04 DAN KOMPOS Azolla pinata UNTUK MENINGKATKAN EFISIENSI BIODEGRADASI HIDROKARBON DALAM PROSES BIOREMEDIASI LIMBAH MINYAK BUMI - Pujawati Suryatmana; Mieke Rochimi Setyawati (Jurnal Agroekoteknologi, 2014)
The Petroleum hydrocarbon waste is one of Pollutant contributing which cause problem in environmental. Azotobacter is a rizobacteria type which is capable fixating dinitrogen. The result investigation showed that Azotobacter sp strain AV04 is capable producing many extra-cellulary biomolecule. That strain AV04 known is capable producing a biomolecule which acting as strong bioemulsifier. Azolla pinata is a hydro plant that can contributes of N, P dan K nutrition to the Soil. This plant has potentialy as a nutrition organic source. The research was focused on the role of the two agents, i.e. Azotobacter sp starin AV04 as the biosurfactan producing bacteria and Azolla pinata composted in the biodegradation hydrocarbon processes. Results showed that the Total Petroleum Hydrocarbon (TPH) efficiency in the 1st week and 5th week, which was in the treatment of 10% (w/w) of A. pinata and 2% (v/w) of Azotobacter sp starin AV04, was reaching in value 56.15 % and 98.03 % respectively. In the optimum treatment showed that the TPH removal efficiency consistently was significantly rising up as long as 5 week period of bioremediation. The residue compounds of Petroleum after one week period incubation on the optimum treatment were constituting hydrocarbon comprise of 26 species of hydrocarbon compound, while at the same time and in the control treatment founded the hydrocarbon compounds remain were still about 37 species of Hydrocarbon compound.